Health Tracking Physician Survey, 2008 (United States) ([Verlag nicht ermittelbar], 2010)
The 2008 Health Tracking Physician Survey (HTPS) is the successor to the Community Tracking Study (CTS) Physician Surveys which were conducted in 1996-1997 (ICPSR 2597), 1998-1999 (ICPSR 3267), 2000-2001 (ICPSR 3820), and 2004-2005 (ICPSR 4584). Unlike the previous surveys, HTPS does not have the community focus intrinsic to CTS. Whereas the CTS design focused on 60 nationally representative communities with sample sizes large enough to draw conclusions about health system change in 12 communities, the HTPS design is a national sample not aimed at measuring change within communities. Hence, "Community" was dropped from the study title. Administered to a nationally representative sample of United States physicians providing direct patient care, HTPS collected information on physician characteristics and specialty distribution; career satisfaction; practice arrangements and ownership; financial interest in medical equipment and hospitals; and physician time allocation, including hours worked, number of office visits, time spent communicating with patients via e-mail and telephone, and provision of charity care. The survey also collected information about the racial and Hispanic-origin composition of patients; percent of patients with chronic conditions; percent of patients with a language barrier; use of interpreter services; sources of practice revenue; level and determinants of physician compensation; use of health information technology; physicians' perception of their ability to deliver care; effects of disease management programs and formal practice guidelines; extent of care coordination; malpractice concerns; and various other aspects of physicians' practice of medicine.